Multiple pregnancy: genetic aspects - Díaz Kuan, Alicia (2015)
Genetic study of gemelarity is a learning continuum. Intense research has not yet determined genes intervening and leading to blastocyst division that originate two identical individuals but possible mechanisms are unveiled as well as differences between monozygotic and dizygotic twins.